A Simple Mathematical Standardized Measurement of Acetabulum Anteversion after Total Hip Arthroplasty. Issue 2 (2008) - Liaw, Chen-Kun; Yang, Rong-Sen; Hou, Sheng-Mou; Wu, Tai-Yin; Fuh, Chiou-Shann
Abstract : We invented a standardization method to measure the cup's anteversion after total hip arthroplasty without the influence of patient's position. We measured 68 radiographs of 10 patients after total hip replacement (THR) and calculated the error of each measurement, defined as the difference with the average of the same measuring method on the same patient. We also calculated the repeatability standard deviation (RSD) of each method according to the American Society for Testing and Materials, ASTM E691. Mean absolute inter-examination angle error, defined as the average of the absolute deviations, was 0.75° for standardized anteversion (range 0.03–2.51°), as compared with those without standardization, 2.30° (range 0.04–13.04°). The inter-examination measurement reliability (precision), defined as one RSD, was 0.99° for standardized anteversion, as compared with those without standarization, 3.50°. There is no difference between patients four and five without ( p = 0.097). There is a significant difference with standardization ( p < 0.0001). Our study demonstrated that this mathematical method is a precise tool to measure the anteversion of the acetabular cup. We hope that it can be used widely in the future.